Lazarus man - Price, Richard, 1949- (Farrar, Straus and Giroux, 2024)
"East Harlem, 2008. In an instant, a five-story tenement collapses into a fuming hill of rubble ... As the city's rescue services and media outlets respond, the surrounding neighborhood descends into chaos. By day's end, six bodies have been recovered but many of the other tenants are missing. In Lazarus Man, Richard Price ... creates intertwining portraits of a group of compelling and singular characters whose lives are permanently affected by the disaster"--